Network security attacks and countermeasures - Kumar G., Dileep 1982-; Singh, Manoj Kumar 1972-; Jayanthi, M. K. 1976- (A volume in Advances in information security, privacy, and ethics (AISPE) book series, 2016)
This book discusses the security and optimization of computer networks for use in a variety of disciplines and fields, touching on such matters as mobile and VPN security, IP spoofing, and intrusion detection